Ontological coaching among nursing undergraduates: a pilot randomized controlled (OCEAN) trial - Travis Lanz-Brian Pereira; Emily Ang; Aayisha; Kuhanesan N. C. Naidu; Yiong Huak Chan; Shefaly Shorey (Medical Education Online)
To develop and assess the preliminary effectiveness of Ontological Coaching Intervention for nursing undergraduates. Design: A pilot randomized controlled trial with a two-group pre-test and post-test followed by process-evaluation qualitative interviews. An Ontological Coaching Intervention was developed through an integration of prior literature and the collective the research team’s experience, consisting of 4-6 sessions over 6-months, each lasting 30-60 minutes. Sessions encompassed exploring ontological coaching concepts, empowering nursing undergraduates to choose topics, and tailoring sessions to individual needs. Sixty undergraduates were recruited; ten were excluded for not completing the baseline questionnaires. Twenty-one nursing undergraduates were randomly assigned to the intervention group and twenty-nine undergraduates to the control group (standard academic support only). Primary (psychological well-being) and secondary (social support quantity and satisfaction, goal-setting, resilience) outcomes were measured at baseline, 3-months, and 6-months. Semi-structured interviews captured post-intervention experiences. Between-group analyses revealed a significant difference in goal-setting scores at 3-months (U = 325.5, p = 0.013), favoring the intervention group (median = 70.50, IQR = 64.25, 76.75). At 6-months, a significant difference in social support satisfaction scores (U = 114.5, p = 0.028) was found between the intervention (median = 33.00, IQR = 29.50, 35.25) and control (median = 30.00, IQR = 30.00, 35.00) groups. However, no significant between-group differences were noted in other outcome measures. Significant within-group differences were found in goal-setting scores at 3- and 6-months in the intervention group and social support quantity scores at 3- and 6-months in the control group. However, no significant within-group differences were noted in other outcome measures. Three themes were identified: Enhanced Holistic Development, Keys to Successful Coaching, and Future Directions for Successful Coaching. There is urgent need to advance research on Ontological Coaching Intervention, particularly, enhancing study rigor, broadening examinations to diverse healthcare student populations and cultural contexts, and addressing identified limitations.